1997
DOI: 10.1093/emboj/16.17.5445
|View full text |Cite
|
Sign up to set email alerts
|

A role for POR1, a Rac1-interacting protein, in ARF6-mediated cytoskeletal rearrangements

Abstract: A role for POR1, a Rac1-interacting protein, in ARF6-mediated cytoskeletal rearrangements in amino acid sequence (Tsuchiya et al., 1991) on the gross morphology of the peripheral membrane remodels the actin cytoskeleton by inducing actin system (Peters et al., 1995). Expression of the wild-type polymerization at the cell periphery. This cytoskeletal and the GTPase-defective mutant, ARF6(Q67L), results rearrangement was inhibited by co-expression of in the elaboration of the plasma membrane characterized ARF6(Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
192
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(206 citation statements)
references
References 48 publications
11
192
3
Order By: Relevance
“…GLUT4 translocation (41), to participate in regulated exocytosis by activating phospholipase D (17,38), to play a regulatory role in receptor-mediated endocytosis (39), to remodel the actin cytoskeleton (34,42), and to be required for phagocytosis in macrophage (43). Our results show that Arf6 also participates in GPCR desensitization.…”
Section: Discussionmentioning
confidence: 75%
“…GLUT4 translocation (41), to participate in regulated exocytosis by activating phospholipase D (17,38), to play a regulatory role in receptor-mediated endocytosis (39), to remodel the actin cytoskeleton (34,42), and to be required for phagocytosis in macrophage (43). Our results show that Arf6 also participates in GPCR desensitization.…”
Section: Discussionmentioning
confidence: 75%
“…However, Arf and Rho family proteins could interact in other ways as well. For instance, Arf could affect the trafficking of Rac (16), or Rho and Arf could together affect the activity of a common protein, such as Partner of Rac (11,59), PtdIns4P 5 kinase (60), or phospholipase D (58). Alternatively, Arf and Rho proteins could reciprocally affect each other's activation or inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are also involved in remodeling the actin cytoskeleton as cells change shape or move. Thus, Arf6 affects endocytosis and phagocytosis, but also regulates the polymerization of cortical actin and cell spreading (9)(10)(11)(12)(13)(14)(15)(16). Arf1 regulates function of the Golgi, endoplasmic reticulum-to-Golgi transport, and recruitment of transport vesicle coat proteins COPI, AP-1, and AP-3, but also affects the recruitment of paxillin to FAs (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Previous studies have suggested a role for ARF6 in regulating Rac1 activity (D'Souza-Schorey et al, 1997;Radhakrishna et al, 1999;Zhang et al, 1999). In an attempt to determine if, in our model system, ARF6 is required for Rac1 activation, we initially investigated whether ARF6 and Rac can associate in an agonist-dependent manner.…”
Section: Ang II Stimulation Promotes the Activation Of Endogenous Arfmentioning
confidence: 99%